Experiência da família rural ao ter o pai/esposo com câncer de próstata - Mathias, Caroline Vieira (2014)
The disease for prostate cancer often leads in changes in physical, psychological, economic factors and social aspects, which can be perceived in the family sphere of the man belongs. The experience of rural families that have the father/husband with diagnosis of prostate cancer reveals itself permeated by the need to reorganization of its dynamics for the role by this person in the family. Thus, this study sought to answer the following question: how the rural families experience to have the disease of the father/husband for prostate cancer? Therefore, this study aimed to describe the experience of rural families to have father/husband receiving treatment for prostate cancer. This is a qualitative approach and descriptive nature. The participants were four families (nine persons) whose father/ husband, stricken with prostate cancer was in cancer treatment at the Hospital Universitário de Santa Maria (HUSM). The research scenario was the residence of the families. A semi-structured interview was the instrument for data collection. The data were collected from March 2013 to February 2014 and the analysis was based on content analysis, thematic modality. As result we organized two categories and six subcategories, discussing early screening of prostate cancer as incipient, being the family essential for the diagnosis. In support of the family identified a process of reorganization and adoption of strategies to assist the man in daily activities, the rehabilitation of the routine itself and in facilitating access to the treatment site. Among the changes of the disease is work in agriculture, role reversal with their spouse, abandonment of leisure activities, affective married life and urinary dysfunction. The difficulties faced during treatment are the side effects of the therapy: decrease or absence of penile erectile function, physiological dysfunctions in eliminations and access to treatment sites. About the motivation to live is to hope for the cure of disease, the future along with the family and the resumption of work life. It was concluded that the family experience on the father/husband with prostate cancer permeates from diagnosis to treatment, dividing tasks, sorrows, hopes and anxieties about an uncertain future.